2012
DOI: 10.2522/ptj.20110371
|View full text |Cite
|
Sign up to set email alerts
|

A Survey of the McKenzie Classification System in the Extremities: Prevalence of Mechanical Syndromes and Preferred Loading Strategies

Abstract: This study demonstrates that trained clinicians can classify patients with extremity problems into MDT classifications and that these classifications remain stable during the treatment episode. Further work is needed to test the efficacy of this system compared with other approaches, but if derangements are as common as this survey suggests, the findings have important prognostic implications because this syndrome is defined by its rapid response to repeated movements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 42 publications
1
31
1
Order By: Relevance
“…Similarly, a recent survey of patients with extremity problems found that 42.7% of those with knee problems were classified as having derangement. 31 Exploratory analyses found knee derangements, when given direction-specific exercises, respond differently to those given standard evidence-based exercises, and whether patients without MDT derangement respond differently to either direction-specific exercises or standard evidence-based exercises. In other words, it remains to be investigated whether a match between classification and specific exercises will result in superior outcomes compared with a mismatch between classification and exercises.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, a recent survey of patients with extremity problems found that 42.7% of those with knee problems were classified as having derangement. 31 Exploratory analyses found knee derangements, when given direction-specific exercises, respond differently to those given standard evidence-based exercises, and whether patients without MDT derangement respond differently to either direction-specific exercises or standard evidence-based exercises. In other words, it remains to be investigated whether a match between classification and specific exercises will result in superior outcomes compared with a mismatch between classification and exercises.…”
Section: Discussionmentioning
confidence: 99%
“…The derangement syndrome has also been reported to exist in the extremities and specifically in the knee. In a recent survey 31 of 103 patients with knee pain, 30 MDT-trained physical therapists classified 42% of the patients as having derangements. Directional preferences in the knee can be either of flexion or extension.…”
Section: T T Conclusionmentioning
confidence: 99%
See 1 more Smart Citation
“…Use of real patients may result in insufficient case mix (Peabody et al, 2000) which may inadvertently introduce sampling bias, especially as it relates to MDT. The Derangement syndrome is the most common classification in the spine (78%, May, 2006) and in the extremity (37%, May & Rosedale, 2012). Because of the apparent prevalence of the Derangement syndrome, the random recruitment of patients may unintentionally create a homogenous sample that potentially would not include all relevant syndromes within the classification system.…”
Section: Clinical Vignettesmentioning
confidence: 99%
“…The OTHER category is made up of 10 diagnostic subgroups which together complete the full MDT classification system where each subgroup has its own definition and diagnostic criteria (Table 2). Table 2 has been modified from the original publication by May and Rosedale (2012) Once completed, the clinician must then pass an oral examination to be awarded Diploma status (http://www.mckenzieinstitute.org/).…”
Section: Mckenzie System Of Mechanical Diagnosis and Therapymentioning
confidence: 99%